The Role of BMI Group on the Impact of Weight Bias Versus Body Positivity Terminology on Behavioral Intentions and Beliefs: An Experimental Study - Stewart, Sarah-Jane F.; Ogden, Jane (Frontiers in Psychology, 2019)
This experimental study investigated the role of BMI on the impact of weight bias versus body positivity terminology on behavioural intentions and beliefs about obesity. Participants (n=332) were randomly allocated to two conditions to receive a vignette depicting an image of a person with obesity using either weight bias (n=164) or body positivity (n=168) terminology. Participants were divided into 3 groups based upon their BMI category (normal weight n=173; overweight n=92; obese n=64). They then completed measures of behavioural intentions, obesity illness beliefs and fat phobia. Although there were several differences in beliefs by BMI group, the results showed no differences between weight bias or body positivity terminology on any measures. There were, however, significant BMI group by condition interactions for beliefs about obesity relating to personal control and treatment control. Post hoc tests showed that weight bias resulted in reduced personal control in the obese BMI group compared to other participants. Weight bias also resulted in higher personal control over obesity in normal weight individuals compared to body positivity. People with obesity reported higher treatment control when exposed to weight bias compared to overweight participants, whereas normal weight participants reported greater treatment control when exposed to body positivity compared to both other groups. To conclude, the impact of weight bias and body positivity information is not universal and varies according to the BMI of the audience and the outcome being measured; whereas people of normal weight may benefit from weight bias there is no evidence that obese people benefit from body positivity. Implications for the prevention and treatment of obesity are discussed.